2019
DOI: 10.1177/1934578x19892688
|View full text |Cite
|
Sign up to set email alerts
|

Systematics Evaluations of Morphological Traits, Chemical Composition, and Antimicrobial Properties of Selected Varieties of Elettaria cardamomum (L.) Maton

Abstract: Elettaria cardamomum is cultivated in the Southern part of India showed great extinct of differences in their morphotypes and chemical compositions. In the present study, we have selected three varieties of Elettaria cardamomum “Valley Green, Palakuzhi, and ICRI”, to analyze the morphological perturbations, chemical compositions, and antimicrobial activities. The differences in the morphological character of cardamom varieties (Valley Green, Palakuzhi, and ICRI) were carried out on the basis of panicles, capsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
(33 reference statements)
4
8
0
Order By: Relevance
“…Considering this, our results reveal that the T. mastichina EO investigated in this study was of the 1,8-cineole chemotype. Studies on E. cardamomum mainly suggest α-terpinyl acetate and 1,8-cineole as major constituents of this EO, which is in accordance with our results [ 16 , 24 , 25 ]. Additionally, some reports indicate that these two components are responsible for the fragrance of this EO [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Considering this, our results reveal that the T. mastichina EO investigated in this study was of the 1,8-cineole chemotype. Studies on E. cardamomum mainly suggest α-terpinyl acetate and 1,8-cineole as major constituents of this EO, which is in accordance with our results [ 16 , 24 , 25 ]. Additionally, some reports indicate that these two components are responsible for the fragrance of this EO [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have reported that for better fragrances, α-terpinyl acetate is always present in higher amount than 1,8 cineole, which may also be an indicator of high-quality E. cardamomum essential oils. In the present study, findings of a higher percentage of α-terpinyl acetate than 1,8 cineole indicated both samples have good quality essential oil similar to earlier reports [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…The content of constituents such as β-trans-ocimene and (+)-2-carene, linalool, Z-citral, trans-geraniol, and (E)-ocimenyl acetate was higher in the EC-G essential oil. These components have also been reported by several investigators [20][21][22][23]. Trans- In the present study, monoterpenes were in higher concentrations in EC-I (83.24%) than in EC-G (73.03%), whereas sesquiterpenes were in higher concentrations in EC-G (18.35%) than in EC-I (9.27%).…”
Section: Discussionsupporting
confidence: 91%
“…Studies have reported that for better fragrances, α-terpinyl acetate is always present in higher amount than 1,8 cineole, which may also be an indicator of high-quality E. cardamomum essential oils; findings of the present study are concurrent with earlier reports [19][20].…”
Section: Discussionsupporting
confidence: 91%